SOURCE OF REPLENISHMENT OF THE ENGLISH VOCABULARY AT THE PRESENT STAGE - Anvarova, Muhlisa; Xoldorova, Hilola (Educational Research in Universal Sciences, 2023)
This article examines one of the effective ways of replenishment of vocabulary in the modern English language. The appearance of a great number of new words and the development of new meanings in the words already available in the language may be largely accounted for by the rapid flow of events, the progress of science and technology and emergence of new concepts in different fields of human activity.